1979
DOI: 10.3382/ps.0581125
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age and Strain on the Relationships between Destructive and Non-Destructive Measurements of Eggshell Strength for White Leghorn Hens

Abstract: Specific gravity, egg and shell weight, compression fracture force (SBS), and nondestructive deformation (DFM) were measured and percent shell, surface area, and shell weight per unit surface area were calculated for a total of 3868 eggs obtained from four strains of Single Comb White Leghorns when the hens were 182, 315, 364, and 497 days of age. Strain and age influenced the measured and calculated variables with SBS and DFM showing the greatest differences. Analyses of variance showed that the y-intercepts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
2
10
1
Order By: Relevance
“…These results agree with those reported by Hamilton et al (1979), but earlier Gowe (1977) and Hamilton (1978b) reported significant differences in albumen quality expressed as Haugh units. Generally, there was little evidence of effects on the egg from changes in the (Na+K)/Cl ratio.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results agree with those reported by Hamilton et al (1979), but earlier Gowe (1977) and Hamilton (1978b) reported significant differences in albumen quality expressed as Haugh units. Generally, there was little evidence of effects on the egg from changes in the (Na+K)/Cl ratio.…”
Section: Resultssupporting
confidence: 92%
“…Shell strength measurements included: specific gravity measured by Archimedes' principle, nondestructive deformation between applied forces of .1 to 1.1 kg, and compression fracture force at 20 mm/sec. Details of nondestructive deformation and compression fracture force measurements have been discussed elsewhere (Hamilton et al, 1979). After weighing the eggs and removing their contents, the shells were carefully washed, dried, and weighed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shell strength was estimated by specific gravity according to the flotation procedure (Voisey and Hamilton, 1977), by non-destructive deformation between applied forces of .1 and 1.1 kg, and by compression factor force at 20 mm/min. Details of the nondestructive deformation and compression fracture force measurements have been discussed elsewhere (Voisey and MacDonald, 1978;Hamilton et al, 1979). All eggs were weighed, the contents removed, and the shells carefully washed with warm tap water, dried, and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…As hens approach the end of the laying year there is a remarkable decrease in shell strength (Hamilton et al, 1979;Potts and Washburn, 1983). Some authors have reported accompanying changes in the organic matrix component of the eggshells from older hens (Fraser et al, 1998;Panheleux et al, 2000).…”
Section: Introductionmentioning
confidence: 99%